The Language of Democracy Political Rhetoric in the United States and Britain, 1790-1900 - Robertson, Andrew W. (Cornell University Press, 2019)
Tracing the history of political rhetoric in nineteenth-century America and Britain, Andrew W. Robertson shows how modern election campaigning was born. Robertson discusses early political cartoons and electioneering speeches as he examines the role of each nation's press in assimilating masses of new voters into the political system.Even a decade after the American Revolution, the author shows, British and American political culture had much in common. On both sides of the Atlantic, electioneering in the 1790s was confined mostly to male elites, and published speeches shared a characteristically neo-classical rhetoric. As voting rights were expanded, however, politicians sought a more effective medium and style for communicating with less-educated audiences. Comparing changes in the modes of discourse in the two countries, Robertson reconstructs the transformation of campaign rhetoric into forms that incorporated the oral culture of the stump speech as well as elite print culture.By the end of the nineteenth century, the press had become the primary medium for initiating, persuading, and sustaining loyal partisan audiences. In Britain and America, millions of men participated in a democratic political culture that spoke their language, played to their prejudices, and courted their approval. Today's readers concerned with broadening political discourse to reach a more diverse audience will find rich and intriguing parallels in Robertson's account